1957
DOI: 10.1149/1.2428558
|View full text |Cite
|
Sign up to set email alerts
|

A Hydrogen Effusion Method for the Determination of Corrosion Rates in Aqueous Systems at Elevated Temperature and Pressure

Abstract: This paper analyzes the limitations of weight change techniques at elevated temperature and pressure, and presents a description of a new technique based on the measurement of the hydrogen generated by the corrosion reaction. This H, which diffuses through the walls of a test specimen containing the aqueous solution, is collected and measured in a vacuum system of known volume which surrounds the test specimen; the corrosion rate is calculated from the hydrogen effusion rate. Results obtained with the techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

1960
1960
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…Berl and Van Taack, who heated small samples of steel powder in a static autoclave for 7.5 hr at 310~ obtained data indicating a minimum in the corrosion rate at a concentration of 0.7 g/1 which corresponds to a pH of 12.24. Some measurements at 316~ by the authors using a more precise static technique, the hydrogen effusion method (9), showed a drop in total corrosion in the region of pH 12.24, and more recent measurements (Table I) confirm the actual minimum in total corrosion at this pH as reported by Berl and Van Taack. Both of these recent studies, however, show that the phenomenon is transitory, and after 25 days the corrosion rate increases monotonically with pH (16).…”
supporting
confidence: 66%
See 1 more Smart Citation
“…Berl and Van Taack, who heated small samples of steel powder in a static autoclave for 7.5 hr at 310~ obtained data indicating a minimum in the corrosion rate at a concentration of 0.7 g/1 which corresponds to a pH of 12.24. Some measurements at 316~ by the authors using a more precise static technique, the hydrogen effusion method (9), showed a drop in total corrosion in the region of pH 12.24, and more recent measurements (Table I) confirm the actual minimum in total corrosion at this pH as reported by Berl and Van Taack. Both of these recent studies, however, show that the phenomenon is transitory, and after 25 days the corrosion rate increases monotonically with pH (16).…”
supporting
confidence: 66%
“…The hydrogen effusion technique employed has been previously described (6,9). It uses as a specimen a small metal capsule filled with the corrosive medium.…”
Section: Methodsmentioning
confidence: 99%
“…Experimental Most of the oxide films examined were formed on the interiors of sealed mild steel capsules filled completely with pH 11 LiOH aqueous solution following the technique devised by Bloom and Krulfeld (10), and heated at 300~ in a circulating air oven. The periods of heating ranged from 30 min to 12 days.…”
mentioning
confidence: 99%
“…This view is also strengthened by Pearse and Afzulpurkar's (73) continuous measurements of corrosion rates by the hydrogen effusion technique (74); these showed a series of peaks in corrosion rate of almost equal magnitude, suggesting that extensive exfoliation of thc 23. This view is also strengthened by Pearse and Afzulpurkar's (73) continuous measurements of corrosion rates by the hydrogen effusion technique (74); these showed a series of peaks in corrosion rate of almost equal magnitude, suggesting that extensive exfoliation of thc 23.…”
Section: Low Ductility Failures In Austenitic Stainless Steels Componmentioning
confidence: 99%